2003
DOI: 10.1373/49.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell-free Fetal DNA as a Second-Trimester Maternal Serum Marker of Down Syndrome Pregnancy

Abstract: Background: Second-trimester cell-free fetal DNA (studied only in pregnancies with male fetuses) is higher in maternal serum samples from women carrying Down syndrome fetuses than in unaffected pregnancies. In this study we evaluated the potential performance of fetal DNA as a screening marker for Down syndrome. Methods: Data on maternal serum fetal DNA concentrations and the corresponding concentrations of the quadruple serum markers were available from 15 Down syndrome cases, each matched for gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 16 publications
2
32
2
5
Order By: Relevance
“…Recently, Skoog et al (11 ) identified a C/A exchange at position Ϫ863 of the TNF-␣ gene promoter and found higher transcriptional activity of the C allele in reporter gene assays. This polymorphic site was found to be associated with thyroid-associated ophthalmopathy (12 ), Crohn disease (13 ), juvenile rheumatoid arthritis (14 ), and the lumbar spine area (15 ).…”
Section: Rapid Genotyping For Tumor Necrosis Factor-␣ (Tnf-␣)mentioning
confidence: 99%
“…Recently, Skoog et al (11 ) identified a C/A exchange at position Ϫ863 of the TNF-␣ gene promoter and found higher transcriptional activity of the C allele in reporter gene assays. This polymorphic site was found to be associated with thyroid-associated ophthalmopathy (12 ), Crohn disease (13 ), juvenile rheumatoid arthritis (14 ), and the lumbar spine area (15 ).…”
Section: Rapid Genotyping For Tumor Necrosis Factor-␣ (Tnf-␣)mentioning
confidence: 99%
“…In addition, quantitative aberrations of circulating fetal DNA have been reported in preeclampsia (10,11 ), preterm labor (12 ), and certain fetal chromosomal aneuploidies (13 ). Despite in-creased circulating fetal DNA concentrations in trisomy 21 pregnancies, there is a large overlap in fetal DNA concentrations between healthy and aneuploid pregnancies (13,14 ). Moreover, these applications are based on the detection of paternally inherited variations or Y chromosomal sequences and thus are useful for only a fraction of all pregnancies unless a large panel of polymorphic markers is used.…”
mentioning
confidence: 99%
“…The ultimate goal in this field is to develop reliable noninvasive tests for clinical prenatal diagnosis. Current applications center on detection of common paternally inherited traits such as sex (3 ) or Rh status (4 ), but recent reports have described methods to screen for or diagnose diseases in the fetus (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%